Predicting of the risk of major cardiovascular events developing in patients with chronic obstructive pulmonary disease in combination with renal dysfunction - E. V. Bolotova; V. V. Yavlyanskaya; A. V. Dudnikova (Кардиоваскулярная терапия и профилактика)
Aim. To identify the independent predictors of major cardiovascular events (MCVE) in patients with chronic obstructive pulmonary disease (COPD) in combination with the early stages of chronic kidney disease (CKD).Material and methods. The study included 279 patients with GOLD 2014 2-4 severity COPD. At the first stage, we surveyed the potential risk factors for MCVE and the level of 25-OH vitamin D. After 12 months, all patients had a history of MCVE. Patients were divided into 2 groups: those who had MCVE during the previous 12 months, and without them. The risk factors for the development of MCVE, significantly differing between the two groups according to the results of a univariate analysis, were included in the logistic regression to determine reliable independent predictors of MCVE. We also studied ROC curve to identify the prognostic cut-off point.Results. The group of patients who had MCVE consisted of 37 people with 40 MCVE cases. In patients with COPD in combination with the early stage of CKD, the level of vitamin D, the frequency of exacerbations in the preceding 12 months, the glomerular filtration rate (GFR), the score of PROCAM scale significantly influence to the development of MCVE. For the constructed regression equation, the determination coefficient is defined as R2=0,76, Hosmer-Lemeshov criterion =0,8. The area under the curve for the model =0,95. According to the results of the ROC analysis, it was found that independent predictors of MCVE in a 12-month period in patients with COPD and CKD (early stages) are: the sum of PROCAM scale points >56, the frequency of COPD exacerbations for the previous 12 months >2, GFR <80 ml/min/1,73 m2, the level of vitamin D <34,3 ng/ml.Conclusion. Independent predictors of MCVE in a 12-month period in patients with COPD and the early stages of CKD are: the score of the PROCAM scale >56, the frequency of exacerbations of COPD in the preceding 12 months >2, GFR <80 ml/min/1,73 m2, the level of vitamin D <34,3 ng/ml.